2019
DOI: 10.3390/ijms20133300
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 Facilitates Runx2 and Osterix Expression by Inhibiting miR-608 through PI3K/Akt Signaling in Osteoblasts

Abstract: CCN3, otherwise known as the nephroblastoma overexpressed (NOV) protein, is a cysteine-rich protein that belongs to the CCN family and regulates several cellular functions. Osteoblasts are major bone-forming cells that undergo proliferation, mineralization, renewal, and repair during the bone formation process. We have previously reported that CCN3 increases bone morphogenetic protein 4 (BMP-4) production and bone mineralization in osteoblasts, although the role of CCN3 remains unclear with regard to osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…However, PSMC6 gene knockout increased the phosphorylation level of PI3K compared with that of 8th week group (Figure 3g). These results suggested that activated PI3K/AKT signaling pathways can reduce apoptosis of osteoporosis‐induced osteoblasts and increase bone mineral density, which is consistent with the above reports (Chen et al, 2019). However, animal experimental studies are not sufficient to reveal the specific mechanism of PSMC6 in ovariectomy‐induced osteoporosis, we would use in vitro experiments to further validate the specific mechanism of PSMC6 in ovariectomy‐induced osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…However, PSMC6 gene knockout increased the phosphorylation level of PI3K compared with that of 8th week group (Figure 3g). These results suggested that activated PI3K/AKT signaling pathways can reduce apoptosis of osteoporosis‐induced osteoblasts and increase bone mineral density, which is consistent with the above reports (Chen et al, 2019). However, animal experimental studies are not sufficient to reveal the specific mechanism of PSMC6 in ovariectomy‐induced osteoporosis, we would use in vitro experiments to further validate the specific mechanism of PSMC6 in ovariectomy‐induced osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…Since CCN3 is known to promote BMP expression and bone formation, 13,14 to examine whether CCN3 is critical factor in prostate cancer CM, the prostate cancer CM was treated with CCN3 antibody. The results showed that CCN3 antibody effectively reduced prostate cancer CM‐promoted increases in BMP, Runx2 and osterix synthesis (Figure 2), indicating that prostate cancer‐derived CCN3 promotes the production of osteogenic factors in osteoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research indicated that CCN3 promotes BMP‐4 production and bone mineralization in osteoblasts 13 . We have also shown that CCN3 enhances osteoblastic differentiation by upregulating Runx2 and osterix, and by inhibiting miR‐608 expression 14 . Conversely, CCN3 reportedly controls prostate osteolytic bone metastasis through RANKL‐dependent osteoclastogenesis 15 .…”
Section: Introductionmentioning
confidence: 96%
“…AKT can also affect osteoblast survival and bone formation by retaining the Forkhead box protein O (FOXOs) in the cytoplasm [ 30 ]. Recent studies have shown that the PI3K/AKT pathway activation up-regulates the osteogenic differentiation markers gene expression, such as BMP2 and ALP, thus stimulating osteoblast differentiation and proliferation [ 31 ]. In contrast, the inhibition of PI3K/AKT signaling activity weakens the bone resportion capacity of osteoclasts [ 32 ].…”
Section: Discussionmentioning
confidence: 99%